2018
DOI: 10.1136/bjophthalmol-2018-312419
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of photodynamic therapy or ranibizumab for polypoidal choroidal vasculopathy in LAPTOP study

Abstract: The better VA in the initial ranibizumab group compared with the PDT group at 2 years was retained at the 5-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
(11 reference statements)
1
12
0
2
Order By: Relevance
“…Since long-term follow-up is difficult in ordinary clinical practice, the number of patients in each treatment group among various subtypes of PCV is relatively small, so that our results might need to be confirmed by further studies which include more subjects. Although we have examined the distribution of various treatment regimens among different subtypes of PCV, bias due to the small number of subjects seems to be unavoidable in such a study, which is similar to previous studies of long-term treatment for PCV [11][12][13][14][15][16]. Moreover, because of the retrospective nature of this study, long-term randomized clinical trials and prospective real-world studies are needed to investigate more effective treatment regimens for PCV according to imaging features.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since long-term follow-up is difficult in ordinary clinical practice, the number of patients in each treatment group among various subtypes of PCV is relatively small, so that our results might need to be confirmed by further studies which include more subjects. Although we have examined the distribution of various treatment regimens among different subtypes of PCV, bias due to the small number of subjects seems to be unavoidable in such a study, which is similar to previous studies of long-term treatment for PCV [11][12][13][14][15][16]. Moreover, because of the retrospective nature of this study, long-term randomized clinical trials and prospective real-world studies are needed to investigate more effective treatment regimens for PCV according to imaging features.…”
Section: Discussionsupporting
confidence: 65%
“…e mean number of anti-VEGF therapies in the present real-world study was less than that in previous studies, which did not classify PCV into various subtypes. An extensive study of the LAPTOP study reported a mean injection number of 14.8 for ranibizumab in the anti-VEGF monotherapy group over 5 years, in which the number of ranibizumab injection was 8.0 in 3 years after the LAPTOP study, while the number of aflibercept was 3.7 [14]. Another Japanese study reported a mean injection number of 18.2 for ranibizumab over 6 years [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The BCVA results were significantly better in the ranibizumab arm and this difference persisted at the 5-year follow-up. 57 EVEREST I compared PDT alone and in combination with ranibizumab with ranibizumab monotherapy in PCV, finding that both PDT arms were superior to ranibizumab alone in terms of ICGA-assessed complete polypoidal lesion regression at 6 months. 58 Because EVEREST I was not powered to determine differences in best-corrected visual acuity (BCVA), EVEREST II was done to compare the combination of PDT and ranibizumab with ranibizumab alone.…”
Section: Anti-vegf Therapymentioning
confidence: 99%
“…Ranibizumab (Lucentis/Accentrix, Novartis, Basel, Switzerland) is a VEGF antibody fragment that neutralizes all isoforms of VEGF-A,[ 63 ] and its efficacy in PCV has been evaluated in a number of studies including the LAPTOP and EVEREST 1 and 2 studies. [ 18 64 65 66 67 68 69 70 71 72 ] The PEARL and PEARL2 studies have demonstrated the short-term efficacy of 0.5 mg and 2 mg ranibizumab in PCV, respectively. Monthly intravitreal ranibizumab was shown to stabilize vision, reduce subretinal hemorrhage, and decrease macular edema.…”
Section: Management Of Pcvmentioning
confidence: 99%